AgInS2 and graphene co-sensitized TiO2 photoanodes for photocathodic protection of Q235 carbon steel under visible light. (8th May 2020) - Li, Hong; Song, Weizhe; Cui, Xingqiang; Li, Yanhui; Hou, Baorong; Zhang, Xiaoping; Wang, Yuqi; Cheng, Lianjun; Zhang, Pengfei; Li, Junru
Abstract: AgInS2 nanoparticle and graphene nanosheet co-sensitized anatase TiO2 nanotube array films were fabricated by a combination of hydrothermal reaction and electrochemical anodization on titanium sheets. The results showed that the co-sensitization of AgInS2 nanoparticles and graphene nanosheets extended the photoresponse of TiO2 nanotubes into the visible-light region, and improved the photogenerated charge separation and transfer capability. The photocurrent density of the AgInS2 /graphene/TiO2 composites (about 4.0 mA cm −2 ) was 20 times that of bare TiO2 (only 0.2 mA cm −2 ) under visible-light illumination. The potential negative shift value of AgInS2 /graphene/TiO2 composites was up to 0.68 V versus saturated calomel electrode. The AgInS2 /graphene/TiO2 composites can provide Q235 carbon steel with highly efficient photocathodic protection under visible-light illumination.